Impact of Ayurvedic Dietetics (Pathya Apathya) in the Management of Tamak Shwasa: A Critical Review (International Journal of Ayurveda and Pharma Research, 2023)
Bronchial Asthma is a major non-communicable disease affecting both children and adults, nearly 262 million people in India suffer from asthma (WHO). It is a chronic disorder that affects the airways and characterized by bronchial hyper-reactivity and reversible airway obstruction. It could be correlated as Tamak shwasa in Ayurveda and considered as Pranvaha srotho vikara. The Pathya Aahar and Vihara, having Vata and Kapha alleviating properties can bring them to normalcy. The preventive and curative aspects of Ayurveda revolve around the central theme of Pathya Aahara and Vihara as Ayurveda advocates that Pathya is the secret of wellness whereas Apathya is the root cause of all diseases. Proper diet and implementation of right life style is necessary for better quality of life. Hence this review article defines the properties of various Pathya and Apathya Aahara Dravyas described in Ayurveda classics with view of modern scientific researches.